Strategy or disaster. Flood prevention related issues and actions in the Tisza River basin - Schweitzer, Ferenc (Hungarian Geographical Bulletin, 2009)
Changes in land use of the lowland landscape along the Tisza River have largely been shaped by processes that took place after flood control and regulation measures of that river. As a result fluvial accumulation has either been eliminated or restricted to the flood plain. At present human settlements extend to some segments of the low flood plain threatened by flood hazard. The amended Vásárhelyi Scheme focuses on raising embankments and extension of flood plain. Floods called the attention to problems that have to be solved, such as the stability of levee slopes. To prevent slope slumps it would be reasonable to start studies on flood control embankments in order to reveal sections endangered by an extreme water pressure during floods.